Efforts to Realize Legal Certainty of Land Ownership in Lampung through Blocking of Land Certificate - Meutia Safitri (Fakultas Hukum Universitas Lampung, 2020)
Article 19 of the UUPA states that land registration is carried out as a way to guarantee legal certainty of land rights. The Land Office will issue a certificate of land rights for rights holders. Therefore, the right holder is obliged to register at the local Land Office if there is a transfer or assignment of rights. This study aims to determine: 1) the legal status of the blocked land certificate, and 2) the legal certainty of the land title certificate when the registration of the block has passed 30 days or there has been a court decision regarding the block. This study uses a normative juridical research method. The approach to the problem used is a statutory approach and a conceptual approach. The data analysis used is qualitative in the form of descriptive analytical. The data source used is in the form of secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research results show that: 1) the legal status of the blocked land title certificate is that transitional legal actions and land rights are imposed. 2) The legal certainty of a land title certificate when the registration of the block has passed 30 days is the restoration of the legal status of the land title certificate holder.